„Ninurta-Duft“ oder: von den Vorsichtsmaßnahmen, die ein mesopotamischer Heiler ergreifen sollte, bevor er einen erkrankten Patienten aufsuchte - Maul, Stefan M. (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2018)
Among the best preserved of the tablets found in the so-called “House of the Incantation Priest” in Assur numbers Tablet VAT 8803, already fired in antiquity, written by the healer Nabû-bēssun(u) in the early 7th century BCE. The accurate, archaising ductus of the script and the many triangular “firing holes” on the obverse, reverse, and side margins furnish this tablet, first published as KAR no. 31, with a striking physical appearance commensurate with its fundamental significance for ancient Near Eastern healing arts. In addition to instructions regarding the preparation and application of a salve which should provide the healer with the necessary sanitary protection when visiting invalids, the tablet also contains the wording of the concomitant exorcistic dicenda. A new edition of this text is here presented.
Gesehen am 04.07.2019